2021
DOI: 10.3390/ijerph18158067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Active Group Music Intervention versus Group Music Listening in Alzheimer’s Disease

Abstract: Background: Music interventions are promising therapies for the management of symptoms in Alzheimer’s disease (AD). Globally, music interventions can be classified as active or receptive depending on the participation of the subjects. Active and receptive music tasks engage different brain areas that might result in distinctive clinical effects. This study aims to compare the clinical effects of two types of music interventions and a control activity. Methods: Ninety AD patients from six nursing homes particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
(51 reference statements)
0
34
0
2
Order By: Relevance
“…Active music intervention can help with Alzheimer's symptoms and should be given as a supplement to standard care. The data demonstrate that combining AMI with standard treatment can help mild-to-moderate AD patients improve their cognition, behavior, and reliance [20].…”
Section: Source Localization Datamentioning
confidence: 82%
“…Active music intervention can help with Alzheimer's symptoms and should be given as a supplement to standard care. The data demonstrate that combining AMI with standard treatment can help mild-to-moderate AD patients improve their cognition, behavior, and reliance [20].…”
Section: Source Localization Datamentioning
confidence: 82%
“…This suggests that active music-based intervention would have positive effects on executive function. This may be because active music intervention is more likely to promote socialization, engagement, verbal processing, or motor planning compared with receptive music intervention [ 66 ]. Since active music intervention has been utilized more often than receptive music intervention, future studies should investigate the effect of active music-based intervention on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that a few studies on effects of AD specifically (not dementia in general) support the conclusion that MT has beneficial effects on cognitive function, behavioral symptoms of dementia, and mood in patients with AD. 19,24,28,55,[57][58][59][60][61]…”
Section: Therapeutic Effects Of Music Therapy For Ad Patientsmentioning
confidence: 99%
“…Although this study demonstrated the promising effects of MT, there are relatively few studies that have investigated AD patients exclusively, 19,24,27,28,55–61 and to the best of our knowledge, no meta‐analyses on the effects of MT in AD are available. A meta‐analysis on effects of MT in dementia patients in general, including dementias other than AD, reported a small effect of active MT on global cognition (but this effect was not present when both active and receptive studies were combined) 62 .…”
Section: Therapeutic Effects Of Music Therapy For Ad Patientsmentioning
confidence: 99%